Impacts of COVID-19 on Labor Markets and Household Well-Being in Pakistan : Evidence From an Online Job Platform - Tas, Emcet O.; Ahmed, Tanima; Matsuda, Norihiko; Nomura, Shinsaku (World Bank, Washington, DC, 2021)
This brief uses the administrative database of Pakistan’s largest online job platform and an online COVID-19 survey to examine the gender impacts of the COVID-19 pandemic on labor markets and other well-being indicators. The analysis shows that the pandemic led to an unprecedented level of economic insecurity, resulting in widespread job loss, business closures, slowdown in business activity, and reduced working hours. The sectors where women are more likely to be employed, such as education and health, were more severely affected, yet the post-pandemic recovery was faster for males. The pandemic has also led to a disproportionate increase in women’s unpaid care work, as well as increasing their reported rates of stress, anxiety and exposure to violence. These findings suggest that impacts resulting from COVID-19 might lead to further declines in women’s participation in the economy in Pakistan, where women’s labor force participation is already among the world’s lowest.